Umm Qays, Jordanien. Das Objekt im Blick. Untersuchung und experimenteller Nachbau. Bauwerkserhaltung im ›alten‹ Dorf von Umm Qays (Jordanien). Die Arbeiten des Jahres 2021 - Zenker, Olga; Bührig, Claudia (e-Forschungsberichte des DAI, 2022)
Integrated into a building conservation training program that has been running since 2016, a team of German craftsmen and Jordanian and Syrian workers restored a former guest and meeting room in the old village of Umm Qays in accordance with the requirements for monument preservation. The restoration measures were based on previous scientific research. Due to the increasing loss of craftmanship, many of the historical construction techniques had to be reacquired on site. It was only through the mutual knowledge gained from research and practice, supplemented by the exchange with the local population, that the measures could be successfully completed.